Distributed Sensing using Mobile Smartphones - Padmanabhan, Venkat (IT Magazine, 2008)
If you thought your smartphone was already doing more than enough by allowing you to send e-mail, browse the Web and do word processing, think again. It might just become part of the distributed sensing revolution that is set to sweep the world.